KERJASAMA UNITED NATIONS HIGH COMMISSION FOR REFUGEES (UNHCR) DAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI MASALAH PENGUNGSI DI KOTA PEKANBARU TAHUN 2017-2021 - Dika Nofira Hardiyanti; Evi Deliana; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Refugees are a classic problem that arises in human civilization as a resultof fear that threatens theis safety. The threat can be caused by natural disasters orman-made disasters. This large-scale population movement was initially only adomestic problem of country. The research objectives of this thesis are ; First, tofind out the cooperation between United Nations High Commission for Refugeesand International Organization for Migration with the Indonesian government indealing with refugee problems in Pekanbaru City in 2017-2021, Second, theIndonesian government’s efforts to urge United Nations High Commissioner forRefugees and International Organization for Migration to place refugees in thirdcountries.This research is a kind of sociological research. This research wasconducted at the Pekanbaru Immigration Detention Center and RepresentativeOffice of UNHCR and IOM Pekanbaru. While the overall population and thesample is related to the problems axamined in this study. The data used is primarydata and secondary data and data collection techniques using observation,interviews and literature study. Technical analysis of qualitative, inductiveinference techniques.From the research results, there are two things that can be concluded.First, the collaboration between UNHCR and IOM with the Indonesia governmentin deling with the refugee problem in Pekanbaru City in 2017-2021. Second, theefforts of the Indonesian government to urge UNHCR and IOM to place refugeesin third countries. Suggestions from the author, First, its is hoped that UNHCRand IOM will be more responsive in dealing with the problem of refugee inIndonesia, especially Pekanbaru. Second, the Indonesian government alwaysmonitors UNHCR and IOM and urges these refugees to be immediately sent totheir destination countries, because Indonesia is only a transit country. InIndonesia they only get housinh, eting and drinking faclilities, and their full rightsas citizens will only be obtained in the destination country, etc.Keywords : Refugees – UNHCR – IOM – Convention 1951 – Third Countries.